2002
DOI: 10.1063/1.1445180
|View full text |Cite
|
Sign up to set email alerts
|

Resonant plasma heating below the cyclotron frequency

Abstract: Resonant heating of a magnetized plasma by low frequency waves of large amplitude is considered. It is shown that the magnetic moment can be changed nonadiabatically by a single large amplitude wave, even at frequencies normally considered nonresonant. Two examples clearly demonstrate the existence of the resonances leading to chaos and the generic nature of heating below the cyclotron frequency. First the classical case of an electrostatic wave of large amplitude propagating across a confining uniform magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 7 publications
(4 reference statements)
4
61
0
Order By: Relevance
“…Second, we confirmed the result of Ref. 9 that the stochasticity threshold can be strongly reduced (by several orders of magnitude) in the presence of many waves, ω n with n = 1, 2, 3...n max 1. However, we found that this will be the case only when ∆ω ≡ |ω n+1 − ω n | ω n , the heating efficiency growing with (∆ω) −1 .…”
Section: Discussionsupporting
confidence: 76%
“…Second, we confirmed the result of Ref. 9 that the stochasticity threshold can be strongly reduced (by several orders of magnitude) in the presence of many waves, ω n with n = 1, 2, 3...n max 1. However, we found that this will be the case only when ∆ω ≡ |ω n+1 − ω n | ω n , the heating efficiency growing with (∆ω) −1 .…”
Section: Discussionsupporting
confidence: 76%
“…Guo et al (2008) further pointed out that the ion heating occurs when the cyclotron resonances at subcyclotron frequencies start to overlap with their corresponding neighboring resonances and then leads to global stochasticity. When a spectrum of Alfvén waves is considered, White et al (2002) demonstrated that the amplitude threshold of the Alfvén waves for ion stochastic heating can be significantly decreased. Evidences of ion heating by low-frequency Alfvén waves have also been found in laboratory experiments (Gates et al 2001;Fredrickson et al 2002;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note the analogy between the fractional resonances and resonant heating below the cyclotron frequency as described in Refs. [9,10]. In the cyclotron case the heating, W c ¼ v ?…”
mentioning
confidence: 99%